Revisiting the Safety of Over-the-Counter Cough and Cold Medications in the Pediatric Population. (April 2014) - Yang, Michele; So, Tsz-Yin
Increased reports of serious adverse events in young children have led to numerous investigations of its therapeutic role in the pediatric population. A review of the literature has shown limited support of its use in young children, with the majority of randomized controlled trials showing no difference in endpoints when compared to placebo. Because of the recent recommended changes to pediatric cough and cold medication use, studies have suggested a decline in ingestion misuses, health care referrals, and reports of adverse events. While these patterns of use are reassuring, clinicians should continue to educate and provide caregivers guidance in managing cough and cold symptoms. Although a tremendous improvement in frequency of therapeutic error ingestions in children younger than 2 years was shown in these studies, the same magnitude of improvement was not seen in children 2 to 12 years. Therefore, future research is necessary to investigate its role in children younger than 12 years.